A STUDY ON THE TEACHERS' REINFORCEMENT IN LEARNING ENGLISH LANGUAGE AT PELITA KASIH KINDERGARTEN - ., Putu Pande Novita Sari; ., Prof. Dr. Ni Nyoman Padmadewi,MA; ., Drs.Gede Batan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2017)
Penelitian ini bertujuan untuk mengetahui (1) jenis-jenis penguatan yang digunakan oleh guru Bahasa Inggris di TK Pelita Kasih, (2) tanggapan siswa terhadap penguatan yang telah diberikan oleh guru di TK Pelita Kasih. Penelitian ini adalah penelitian deskripsi kualititatif. Subjek dari penelitian ini adalah guru Bahasa Inggris dan siswa di TK Pelita Kasih. Metode pengumpulan data yang digunakan melalui observasi, wawancara dan dokumentasi. Selain itu, perekam suara, wawancara dan catatan juga digunakan untuk memperoleh data. Hasil dari penelitian ini menunjukan guru Bahasa Inggris di TK Pelita Kasih menggunakan dua jenis penguatan yaitu penguatan positif dan negatif. Penguatan positif verbal seperti good, very good, good job, good boy/girl, great, well done, smart student, nice, right and wonderful. Sedangkan, penguatan positif verbal star, applause, smile, touch the students, giving priority, nodding head, thumb up and hi five. Penguatan positif verbal lebih sering digunakan oleh guru untuk memotivasi siswa dalam belajar. Sedangkan, penguatan negatif verbal seperti negotiation (giving choices), calling names and giving explanation. Selain itu, penguatan negatif nonverbal silent chair and time out. Guru Bahasa Inggris menggunakan penguatan negatif sebegai konsekuensi. Penguatan negatif yang diberikan oleh guru bertujuan untuk mengurangi tingkah laku siswa yang kurang baik dalam proses belajar. Hasil dari observasi menunjukan siswa memberikan respon positif dan negatif ketika guru memberikan penguatan. Respon positif lebih sering diberikan oleh siswa. Kata Kunci : penguatan, respon, positif, negatif, verbal, nonverbal This study aimed at finding out (1) the types of reinforcement used by the English teachers at Pelita Kasih Kindergarten (2) the students’ responses toward the teachers’ reinforcement used by the English teachers. This study was descriptive qualitative research. The subject of this study were the English teachers and the students of Pelita Kasih Kindergarten. The data were collected through direct observation, interview and documentation. Besides, mobile recorder, interview guide and field note were also used to collect the data. The results of this study showed that the English teachers at Pelita Kasih Kindergarten used two kinds of reinforcements there were positive and negative reinforcement in form of verbal and nonverbal reinforcement. Positive verbal reinforcement such as good, very good, good job, good boy/girl, great, well done, smart student, nice, right and wonderful. Meanwhile, positive verbal reinforcement such as star, applause, smile, touch the students, giving priority, nodding head, thumb up and hi five. Positive verbal reinforcement was most frequently used by the teachers to motivate the students during the learning process. Meanwhile, negative verbal reinforcement such as negotiation (giving choices), calling names and giving explanation. Moreover, negative nonverbal reinforcement such as silent chair and time out. The English teachers used negative reinforcement as consequences. Negative reinforcement given by the teacher aimed to decrease students’ inappropriate behavior in the learning process. The result of observation also showed that the students gave expected and unexpected response when the teachers delivered reinforcement to the students. Positive response (expected) that was most frequently gave by the students. keyword : reinforcement, responses, positive, negative, verbal, nonverbal